2021
DOI: 10.1007/s11431-021-1934-5
|View full text |Cite
|
Sign up to set email alerts
|

A lithosphere-atmosphere-ionosphere coupling model for ELF electromagnetic waves radiated from seismic sources and its possibility observed by the CSES

Abstract: Over the last century, abnormal electromagnetic (EM) emissions associated with earthquake (EQ) activities have been widely reported and recorded by ground-based and satellite observations. The mechanism of extremely low-frequency (ELF) EM waves radiated from earthquakes has been gradually established. However, whether EM waves radiated from earthquakes can be detected by low Earth orbit (LEO) satellites remains controversial. In this paper, to address these concerns, a lithosphereatmosphere-ionosphere model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…It can be well understood from Figures 2, 3 by Zhao et al (2021) that the wave power of the EM waves radiated by the EQs with a magnitude greater than 6.0 can propagate to high altitudes. At CSES's orbit space, the wave power can sustain a higher level (-0-20 dB) at the frequency band from 20 Hz to 1000 Hz; and at a frequency higher than 1000 Hz, the wave power dramatically declines to below 0 dB.…”
Section: Figure 10mentioning
confidence: 91%
See 2 more Smart Citations
“…It can be well understood from Figures 2, 3 by Zhao et al (2021) that the wave power of the EM waves radiated by the EQs with a magnitude greater than 6.0 can propagate to high altitudes. At CSES's orbit space, the wave power can sustain a higher level (-0-20 dB) at the frequency band from 20 Hz to 1000 Hz; and at a frequency higher than 1000 Hz, the wave power dramatically declines to below 0 dB.…”
Section: Figure 10mentioning
confidence: 91%
“…Additionally, the lower the depth, the lower frequency of waves that can be observed by satellite. The simulation from Zhao et al (2021) suggests that the EM waves radiated from an EQ with a magnitude more than 6.0 can be recorded by CSES, but there exists a dominant frequency band for waves radiated from the epicenters with depths from 20 km to 10 km in the lithosphere. The dominant frequency is about 300 Hz for a source with a 10 km depth and the dominant frequency might be 100 Hz for a depth of 20 km.…”
Section: Figure 10mentioning
confidence: 98%
See 1 more Smart Citation
“…In recent years, with the improvement of electromagnetic observation technology, the anomalous disturbances of the ionospheric electric field before strong earthquakes have been observed by various means (Ouzounov et al, 2007;Liu et al, 2010;Pulinets et al, 2018). The ground-based electromagnetic observation and simulation experimental study revealed anomalous pre-earthquake ionospheric electric field disturbances in a wide frequency band, especially in the very-low-frequency/ ultra-low-frequency (ELF/VLF) band, which is easily observed (Zhao et al, 2021). Gokhberg et al (1982) first discovered anomalous disturbances in electromagnetic signals before earthquakes by satellite.…”
Section: Introductionmentioning
confidence: 99%
“…Following the launch of the China Seismo-Electromagnetic Satellite (CSES) on February 2, 2018, a series of studies have been conducted in various areas. These include data availability (Yan et al, 2020;Liu et al, 2021), global geomagnetic models , ionospheric events such as magnetic storms (Spogli et al, 2021), statistical characteristics of seismic ionospheric disturbances (Li et al, 2020; De Santis et al, 2021), and multi-layer coupling (Marchetti et al, 2019;Zhao et al, 2021;Liu et al, 2023;.…”
Section: Introductionmentioning
confidence: 99%